Pyricularia oryzae: virulência de isolamentos, densidade de conídios no ar e efeito do nitrogênio na suscetibilidade do trigo - Danelli, Anderson Luiz Durante (2015)
The wheat blast, caused by the fungus Pyricularia oryzae, is a limiting disease for the wheat crop in Brazil. To check the pathotype variability in a population of isolates of P. oryzae from wheat and other Poaceae specie, we developed a weekly inoculation schedule on a series of differential varieties. The isolates were characterized in relation to the response on seedlings and on adult plants (detached head). The virulence spectrum indicated a population with a high degree of variation and the occurrence of the isolates from invasive from invasive grasses similar virulence to wheat isolates. To determine the relationship of P. oryzae airborne propagules and weather variables and the occurrence of blast in Passo Fundo, Rio Grande do Sul, we monitored the presence or absence of conidia of P. oryzae between February 2nd 2013 and June 7th , 2014, with the help of a collecting spore trap and glass slides smeared with vaseline. The presence of conidia flow P. oryzae in Passo Fundo, was detected. The important predictors of spores release were average relative humidity, mean daily temperature, less than 5 mm day-1, precipitation numbers of hours in which the temperature was between 15 and 35 °C and relative humidity > 93%. The influence of the increase of nitrogen applied at the base of the plants, on the severity of the blast on wheat heads, was evaluated on wheat genotypes. The application of increasing doses of N in the base, up to 200 kg ha-1 of urea, increased the severity of head blast. Wheat cultivars with different degrees of blast resistance did not differ in their reaction to the disease when submitted to the application of increasing doses of N in the base